Perancangan Sistem Informasi Eksekutif Tridharma Perguruan Tinggi Universitas Duta Bangsa Surakarta Dengan Service Oriented Architecture (SOA) - Khoirul Mustofa; M Suyanto; Sudarmawan Sudarmawan (Politeknik Indonusa Surakarta, 2020)
The design of the tri dharma college executive information system is used to assist in making decisions. The university tri dharma executive information system aims to determine the performance of lecturers in the implementation of tri dharma. Executive information system design and executive information system analysis are used in achieving research objectives. Information from the use of the executive information system produces a summary of the performance of lecturers in the implementation of the tri dharma.